Effect of deep work on the green blood system - K.Komilov; D.Komilova; O.Mo’minova (Academia Open, 2019)
The result of the study have been scientifically proven to be the best agro-technology for the formation, growth and cultivation of high-quality cotton yields by differentiating inter-row cultivation in the conditions of ancient irrigated and original soils of Andijan region